Konflik batin pada tokoh utama dalam novel lost in Ningxia karya Asma Nadia - Nathaniela, Audrey Olga Dzakiyya; Israhayu, Eko Sri (Karoteh Utama, 2025)
This study aims to describe the forms of inner conflict and identify the most dominant type of conflict experienced by the main character in the novel Lost in Ningxia by Asma Nadia. The study employs a literary psychology approach based on Kurt Lewin's conflict theory, which classifies conflict into three main types: approach-approach, avoidance-avoidance, and approach-avoidance. The method used is descriptive qualitative, with library research as the data collection technique. The analysis reveals that the main character experiences all three types of inner conflict; however, the approach-avoidance conflict emerges as the most dominant. This type of conflict arises when the character feels drawn to make a decision due to its promising outcome, yet simultaneously feels fear or hesitation due to potential negative consequences. Psychological, social, and spiritual factors serve as the primary triggers of these conflicts, significantly influencing character development and the narrative's direction. This study reinforces the relevance of Lewin’s theory in analyzing the psychological dynamics of literary characters and contributes to literary psychology studies, particularly in exploring complex internal dilemmas related to identity and life transitions.